A representação das pessoas em situação de rua na região metropolitana de Vitória em reportagens do jornal a Gazeta/ES - Toledo, Weliton (2019)
The socialization of the research results reflects the debate on the complex theme in the historical-social context involving homeless people in the metropolitan region of Vitória / ES. For this purpose, the research analyzed 29 articles published in the newspaper capixaba A Gazeta, from January 2015 to June 2017, concerning the approach of the subject to understand how the discursive role of journalism can give social legitimacy to certain narratives that have crystallized throughout our history, grounded in the belief in objectivity and impartiality. Never theless, in the analysis under the plan of what is the “street situation” such problematization goes far beyond the sad narrative and individual experience of each of these people; because in the macro sense we have other issues regarding urban conflicts immersed in the landscape of big cities and public policies aimed at this public. In order to discuss the subject in a minimal way from the perspective of Social Sciences thought, we chose as main theoretical references: Michel Foucault and the power relations in the social environment and the role of biopolitics in the narrative of how mediation between the State occurs. , society and the individual; Karl Marx, who, by inserting the question of structures in the laying down of the bases of capitalist production by the separation of labor from property, gives rise to reasons about the process we are now presenting; or Teun A. van Dijk's linguistic assumptions about the dimension of Critical Discourse Analysis. In the Brazilian case, Florestan Fernandes discusses the genesis of our social inequalities and ills resulting from enslavement; conditions imposed, according to Jessé Souza, by the strong influence of Brazilian rural patriarchalism in the formation of our national identity. In this context, the research found that the reinforcement of the ideologies of hegemonic segments and their power of control with the media sectors - which reproduces the thought / discourse of the country's elites as a way of maintaining the status quo - and the state, remains present. in their inability to formulate public policies that can transform the lives of homeless people (minorities) and reduce historical social inequalities.